Decentralization of public-sector agricultural extension in India: The case of the district-level Agricultural Technology Management Agency (ATMA) - Glendenning, Claire J.; Babu, Suresh Chandra (International Food Policy Research Institute, 2011)
In an effort to increase the impact of extension on agricultural and pro-poor growth in developing countries, public-sector agricultural extension systems around the globe are implementing reforms that include demand-driven and decentralized approaches. Such reforms attempt to increase the accountability of agricultural extension staff to their clients (the farmers) and increase the relevance of extension activities. India is no exception to these trends and has implemented a number of programs to revitalize the public-sector agricultural extension system in the last decade. One such initiative is a central project called Agricultural Technology Management Agency (ATMA). The district-level ATMA project is often highlighted as an innovative model of public-sector agricultural extension involving decentralization as well as participatory and bottom-up approaches. ATMA represents a unique institutional platform that aims to integrate at the district level the weakly linked research and administration arms of public-sector agricultural extension in India. Since the pilot study in 28 districts of India from 1998 to 2003, ATMA has been scaled up to all 591 development districts of India over the five years from 2005 to 2010. Despite empirical impact studies of the ATMA pilot, there is very little evidence of impacts of ATMA post-pilot, but national implementation of ATMA has been varied. A June 2010 revision has attempted to address the constraints the project has experienced over the past five years. This paper examines the evolution and spread of ATMA over the last decade and considers some of the challenges of national implementation of a decentralized process in the public-sector extension system of India. Using primary and secondary sources, in addition to interviews and discussions gathered at a recent national workshop, this paper examines whether the inherent organizational capacity, culture, and management within the public-sector extension system has been addressed by ATMA during the pilot period, during the national scale-up, and now under the revision guidelines. Using an organizational capacity framework, the paper concludes that despite the ambitions of the program, the inherent capacity and culture of public-sector agricultural extension in India, where limited organizational learning from implementation process is taking place, limits the ability of ATMA to fulfill its original objectives.